Employee Performance Improvement Strategy at Hermina Hospital Ciputat - Ruhaedi, Rudi; Hamsinah, Hamsinah; Rusilowati, Umi (Pasundan Social Science Development, 2025)
This study aims to analyze strategies for improving employee performance at Hermina Ciputat Hospital by applying the Analytical Hierarchy Process (AHP) method. The main problem faced by the hospital lies in declining productivity and performance gaps between service units. A quantitative descriptive approach was used to identify the most influential factors contributing to performance improvement, focusing on four main criteria: competence, motivation, training, and reward systems. Data were collected through questionnaires and interviews involving 30 respondents, consisting of medical staff, paramedics, and administrative employees. The AHP method was employed to calculate the priority weights and consistency ratios of each factor. The results revealed that competence had the highest priority weight (0.43), followed by motivation (0.27), training (0.19), and reward systems (0.11), with a consistency ratio (CR) of 0.04, indicating valid consistency. These findings highlight that improving employee competence through continuous training programs is the most effective strategy to enhance performance. Furthermore, employee motivation should be strengthened by implementing fair reward policies, encouraging participation in decision-making, and fostering a collaborative work culture. This study contributes to the development of strategic human resource management policies in hospitals, particularly in enhancing employee performance through competency-based approaches. The results are expected to serve as a practical guide for Hermina Ciputat Hospital management in implementing sustainable performance improvement strategies.